Pengaruh Higienis Pelayanan Cita Rasa Terhadap Kepuasan Pengunjung (Studi Kasus Sate Bulayak Surya Angkringan) - afifudin; Sesa Mia Audenada; Samsul Karmaen; hariono (Al-Qardhu, 2025)
This research is motivated by a lack of attention to food processing and good service methods, as well as the right taste. Hygiene is an effort to prevent disease that focuses on personal or human health efforts and the environment in which the person is located. Service is the action and ability of employees in providing the best and quality service to consumers. Taste is a way of choosing food that must be distinguished from the taste of the food. The methods and approaches used in this study are quantitative research methods that use quantitative. The sample used in this study was 100 people. The techniques used in collecting data are observation and questionnaires (questionnaire). The data analysis techniques used by researchers are the Validity Test, Reliability Test, Hypothesis Test (T Test), Classical Assumption Test. from the results of the reliability test of the four variables that the alpha value calculated for the Attention variable was 0.612 > 0.60, the Interest variable was 0.714 > 0.60. Desire 0.678 > 0.60 and Action 0.669 > 0.60. Thus, the four research instrument variables are declared reliable. If the f-count is greater than the f-table and the probability value is significant <0.05, the regression model is said to be significant. Conversely, if the f-count is smaller than the f-table and the probability value is significant > 0.05, the regression model is said to be insignificant. With a significant level of 0.05, df1 (N1) = k-1 = 4-1 = 3 and df2 (N2) = n-k = 100-4 = 96, where k is the number of variables and n is the number of samples. Then the f-table value in this study is 2.70.